188k views
3 votes
Simplify the expression without a calculator. Use the properties of logarithms.log6 9 + log6 4 =

User Scorpius
by
5.5k points

1 Answer

3 votes

We have the next expression


\log _69+\log _64

And we must simplify it

1. we must use the next property of logarithms


\log _b(xy)=\log _bx+\log _by

In this case,


\log _69+\log _64=\log _6(9\cdot4)=\log _636

2. Using the definition of logarithms


b^a=x\text{ if and only if }\log _bx=a

In this case,


\begin{gathered} 6^x=36 \\ \text{then,} \\ x=2 \end{gathered}

Finally,


\log _69+\log _64=2

ANSWER:


\log _69+\log _64=2

User HeyNow
by
4.9k points